Design and development of a flexible robotic arm vision system for orthopedic robot - Thayabaren Ganesan (2012)
One of the main and recent problems in Malaysian hospitals is the lack of surgeons and specialists, especially in rural areas. Insufficient specialised surgeons in such regions particularly in the niche of orthopaedic causes more fatalities and amputees due to time constrain in attending the patients. Broken limbs due to accidents can be treated and recovered. But severed blood vessels results in blood loss and leads to amputation or even worst fatalities. A mobile robotic system known as OTOROB is designed and developed to aid orthopaedic surgeons to be virtually present at such areas for attending patients. The developed mobile robotic platform requires a flexible robotic arm vision system to be controlled remotely by the surgeon. To be present virtually is still insufficient if clearer view is not obtained. Thus, a flexible robotic arm with vision system as end effector is designed, developed and tested in real time. Prior to the development of the prototype, virtual modelling of the robotic arm is done in Solidworks. The designed model is simulated and analysed to study the suitability of the design. The simulation results proved that the design is applicable. Then, the developed prototype is subjected to repeatability, and linearity tests in order to determine the movement control of the robotic arm. The robotic arm linear and angular movements resulted in less than 5% of error. A Graphical User Interface (GUI) is developed to control the robotic arm and obtain data from the robotic arm regarding the orientation and position. Fuzzy logic is implemented in the control system to provide safety for the robotic arm articulation. The safety systems of the robotic arm consist of Danger Monitoring System (OMS), Obstacle Avoidance System (OAS) and Fail Safe and Auto Recovery System (FSARS). The fuzzy controlled OMS system was tested and evaluated. The results prove that the OMS is capable of conveying danger level surrounding the robotic arm to the user through GUI with warning indication and obstacle positions. While, the developed OAS, responded to the approaching and static obstacle around the robotic arm. The robotic arm is capable of avoiding approaching obstacle autonomously via fuzzy control. FSARS of the robotic arm was subjected to various failure circumstances and the system executed the recovery system successfully. Finally, the vision system was evaluated by analysing the vision lighting system using Matlab software. The integration of LED lighting system improved the visual clarity obtained through the video camera. The smooth control of the robotic arm coupled with the safety routines improved the overall articulation of the robotic arm.